Proposta de implementação de melhorias no processo de execução das obras de distribuição de energia elétrica : aplicado a uma empresa prestadora de serviços - Carvalho, Lucas de (2012)
The need for the supply of electricity is growing in Brazil and the world, thus, works on power distribution networks are necessary. For the execution of these works, there are several interventions in the productive process and constructive networks, which makes the quality a premise to meet the technical specifications for construction and regulatory deadlines. Most of the electricity distribution companies in Brazil, held contracts for works to build global networks through contractors. The electric utility, responsible for the region of Passo Fundo, RS, is included in this context, which justifies this research, which aims to propose reducing rework in the works in distribution networks of electricity. Data refers to the process of planning, implementing forms, process management works in distribution networks were collected on third party service provider, with the local power utility, through documentary research, meetings, visits, direct observations and photographic records. Obtained as search results characterizing the process of planning and execution, the diagnosis of the current management system of flaws in building networks. Management practices were evaluated by the contractor and a proposal was drawn up by which it was possible to introduce actions to improve process management in the construction of distribution networks for electricity, as well as the implementation of these actions in the process of execution of works. Following submission of proposals and adoption of actions observed reduction index rework, postimplementation and was reversing the upward trend of the defects in the executions of improvement works in networks run by the company under study. It is concluded that the proposal for improvement in managing the construction of power grids become more assertive operational process for works on distribution networks and stocks have directed the focus correctly with the causes for treatment effects.